Self Diagnosis (Smart) Plant - Muhd Ihsan Izzat , Rosli (UTeM, 2009)

(untitled)
This project is about to develop smart plant· that will embed possible fault that could occur in process plant. The fault databases have been be written using VB. programming. One of the good features this system will have is that, it will shorten the time taken to identify and rectify that fault. As to make the system become more efficient and user friendly, the Graphical User Interface (GUI) has been be developed using eX-Designer that will be utilized for data supervisory, monitoring and control system for the whole process plant that has been chose. This system will stored all the alarm history into database and can monitor current alarm that could occur in process plant.